PENGGUNAAN LEVEL SUKROSA TERHADAP SIFAT SENSORIS KEFIR SUSU SAPI - Rumeen, Steviana F.J.; Yelnetty, A.; Tamasoleng, M.; Lontaan, Nova (ZOOTEC, 2018)
UTILIZATION OF SEVERAL SUCROSE LEVELS ON SENSORY CHARACTERISTICS OF COWS MILK. The present study was conducted to investigate the utilization of several sucrose levels on sensory characteristics of cow milk kefir. Materials used in the study were: UHT milk, grain kefir, skim milk, sucrose, distilled water (aquadest), alcohol, spiritus or methylated spirit. A Completely Randomized Design (CRD) with 5 treatments and 40 replications (panelists) was used in the present study. Treatments were formulated as follow: A0= sucrose 0% + grain kefir 5%, A1= sucrose 2% + grain kefir 5%, A2= sucrose 4% + grain kefir 5%, A3= sucrose 6% + grain kefir 5%, and A4= sucrose 8% + grain kefir 5%. Sensory test was conducted using hedonic scales. Variables measured were: sensory characteristics consisted of colors, aroma, viscosity, and taste. Tukey test was further employed to analyze treatment differences. Different between treatment(s) was declared at P < 0.05. Research results showed that sucrose levels at 0%, 2%, 4%, 6%, 8% treatments gave a significant effect (P < 0.01) on aroma, viscosity, and taste, but color was not affected (P > 0.05) by treatments. It can be concluded that the utilization of sucrose at the level of 6% (A3) as most preferred by panelists based on sensory characteristics colors, aroma, viscosity, and taste. Keywords : Kefir, Grain Kefir, Sucrose, Sensory